Functional Integration of Embryonic Stem Cell-Derived Neurons in Hippocampal Slice Cultures - Felix Benninger; Heinz Beck; Marius Wernig; Kerry L. Tucker; Oliver Brüstle; Björn Scheffler (2003)
The generation of neurons and glia from pluripotent embryonic stem (ES) cells represents a promising strategy for the study of CNS development and repair. ES cell-derived neural precursors have been shown to develop into morphologically mature neurons and glia when grafted into brain and spinal cord. However, there is a surprising shortage of data concerning the functional integration of ES cell-derived neurons (ESNs) into the host CNS tissue. Here, we use ES cells engineered to express enhanced green fluorescent protein (EGFP) only in neuronal progeny to study the functional properties of ESNs during integration into long-term hippocampal slice cultures. After incorporation into the dentate gyrus, EGFP+ donor neurons display a gradual maturation of their intrinsic discharge behavior and a concomitant increase in the density of voltage-gated Na+ and K+ channels. Integrated ESNs express AMPA and GABA(A) receptor subunits. Most importantly, neurons derived from ES cells receive functional glutamatergic and GABAergic synapses from host neurons. Specifically, we demonstrate that host perforant path axons form synapses onto integrated ESNs. These synapses between host and ES cell-derived neurons display pronounced paired-pulse facilitation indicative of intact presynaptic short-term plasticity. Thus, ES cell-derived neural precursors generate functionally active neurons capable of integrating into the brain circuitry.